Damage to cerebellocortical pathways after closed head injury: a behavioural and magnetic resonance imaging study. Issue 4 (April 1995) - Haggard, P; Miall, R C; Wade, D; Fowler, S; Richardson, A; Anslow, P; Stein, J
Abstract : The objective was to investigate the anatomical substrate of ataxia seen after severe head injury. Five patients were recruited from present and former inpatients at Rivermead Rehabilitation Centre. All patients had had a closed head injury and all had cerebellar type ataxia. Four normal controls were also studied. Brain MRI, clinical examination, computer based recording, and analysis of visuomotor tracking were carried out. Focal damage was found in the superior cerebellar peduncle in all five ataxic patients. The patients' tracking movements showed profound tremor, and unusual reliance on visual feedback. Ataxia seen after severe head injury can arise from damage to the superior cerebellar peduncle, which may interfere with the cerebellocortical circuits involved in coordinated movement.